Never say never: circumventing a contraindication to control apnoea-induced epileptic events with a mandibular advancement device. Issue 11 (5th November 2018) - Fenton, J E; Fitzgerald, C; Dillon, P J; O'Shea, D
Abstract: Background: The benefit of mandibular advancement devices in patients with sleep-disordered breathing and as a potential option for obstructive sleep apnoea syndrome is well recognised. Their use in the setting of epilepsy or other seizure disorders is typically contraindicated. Case report: A 48-year-old patient with a history of poorly controlled epilepsy and obstructive sleep apnoea syndrome was referred for ENT review for possible tracheostomy. The patient was wheelchair-bound with 24-hour continuous positive airway pressure, but sleep studies demonstrated persistent, severe episodes of apnoea and notable sleep disturbance. Sleep nasendoscopy demonstrated marked improvement on capnography with the laryngeal mask airway in situ, and this was maintained with mandibular advancement using jaw thrust following removal of the laryngeal mask airway. A mandibular advancement device was subsequently trialled; this had no subjective benefit for the patient, but the seizures resolved and control of apnoea was achieved with the combination of a mandibular advancement device and continuous positive airway pressure. Conclusion: This paper highlights a novel application of mandibular advancement devices, used in combination with continuous positive airway pressure, which resulted in complete resolution of sleep deprivation and apnoea-induced epileptic events.